Commitment to sport and its relationship to the preferred behavior of the sports coach From the point of view of coaches - amara nouri, (sports creativity, 2025)
General question: Does the attribute of commitment have a correlative relation to the coach's preferred behavior from the point of view of coaches in football? General Hypothesis: There is a correlative relationship to the attribute of commitment to the preferred behavior of the sports coach from the point of view of coaches in football. Partial questions: - The attribute of commitment is related to the training behavior of the sports coach. research goals: - Definition of personality and characteristics and their impact on the process of training sports. - Access to high levels in the sports field stems from the attention first of the psychological side of the sports coach.. Conclusion and suggestions: - Taking into account the integrated preparation of the player in terms of physical, technical, schematic, psychological and mental. - Sense of individual differences between the players as well as the requirements of the player outside the training process. - Excellence in accuracy in planning, organization and continuity and on scientific basis through the organization of methods and methods of training. - The instructor must achieve during his work the educational duty and the educational, training and technical duty. - The coach must be a believer and a lover of his work, convinced to strengthen and raise and train players to reach the upper levels. - To be professionally prepared so that he can progress continuously. - Be able to choose the appropriate and expressive ideas clearly expressed. - The coach should be an example and an example to follow because it is the ideal for his players.